PLANNING STRATEGY ON ADDITIONAL LESSONS TO IMPROVE THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION - Azmi, Ulil (Journal of Educational Administration, 2022)
The planning strategy for additional lessons to improve the quality of Islamic religious education is carried out by providing additional lessons targeted at final class students. Education is not only the responsibility of parents, educational institutions or the government, but a shared responsibility. the strategy and role of the Islamic Religious Education teacher as the most important part of an educational institution, which does not only transfer knowledge but also relates to the values ​​of implementing daily worship, so that teachers are required to be able to choose various kinds of appropriate learning strategies and roles as a competent teacher, thus the goal of improving the quality of student learning can be achieved. Implementation of learning, carried out at times outside of school hours to run effectively. Student achievement after participating in learning that is held outside of school hours is expected to get good and satisfying results. The implementation of learning outside of school hours is expected to be effective and efficient by utilizing students' free time, and to be carried out with a concept and effective time management that does not appear to be forcing students.